Influence of boriding treatment on the mechanical properties of Monel 400 - Christian Pacheco; Jefferson Luiz Jeronimo; Anael Preman Krelling; Cesar Edil da Costa; Júlio Cesar Giubilei Milan (Results in Surfaces and Interfaces)
The Monel 400 nickel-copper alloy exhibits high corrosion resistance but low wear resistance. The boriding thermochemical treatment aims to improve wear resistance by increasing the surface of the material hardness. Previous studies on boriding Monel 400 and other nickel alloys, using boriding powder containing iron and silicon and high treatment temperatures, indicate that these factors may promote material oxidation and reduce the thickness of the nickel boride layer. In this study, a powder composed of 90 wt% B4C and 10 wt% KBF4 was used to boride Monel 400 samples at three different temperatures and treatment times, resulting in varying layer thicknesses. Microstructural characterization was conducted using confocal microscopy, microhardness testing, Scanning Electron Microscopy (SEM), and Energy Dispersive Spectroscopy (EDS). X-ray Diffraction (XRD) was used to determine the phases present. The boron activation energy, determined through kinetic diffusion theory, was found to be 157.2 kJ mol−1. To validate the experimental results, predicted layer thicknesses based on activation energy were compared with experimental boride layer thicknesses from validation samples. The comparison revealed a standard deviation of 11.80% for samples treated at 825 °C for 3 h and 18.65% for samples treated at 875 °C for 3 h. Additionally, instrumented indentation analysis was performed on each sample. A more comprehensive study was conducted on samples treated at 850 °C for 4 h, which included mapping of hardness and Young's Modulus from the layer region to the substrate. This analysis revealed the formation of distinct regions: (I) nickel borided region, (II) diffusion of borides at the grain boundaries, and (III) substrate. Furthermore, copper agglomeration was observed between regions (I) and (II).